Устройство для регистрации полной индикатрисы рассеяния: полезная модель - Тихомиров И. А. Иван Арсентьевич; Цимбал В. Н.; Мышкин В. Ф. Вячеслав Фёдорович; Власов В. А. Виктор Алексеевич
опубл. 16.12.99